(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The structural mechanics module of the OOFEM finite element software has been developed to include various algorithms for solving contact mechanics problems. After developing small strain contact algorithms in the 2D domain and their extension to large strain applications [1, 2], the present contribution extends the existing framework to the 3D domain. After reviewing the current code and comparing existing solutions found in the literature, we identify the common ground between 2D and 3D applications, then propose and implement the necessary changes and additions to smoothly integrate the 3D support into existing code. Tests and example problems are presented to confirm the functionality of the resulting implementation.